Complex Effects of International Relations : Intended and Unintended Consequences of Human Actions in Middle East Conflicts - Israeli, Ofer (Book collections on Project MUSE., 2020)
"Identifies the many ways in which unexpected outcomes are endemic to international relations due to the complexity of world politics"--